Suprachiasmatic nucleus dysfunction induces anxiety- and depression-like behaviors via activating the BDNF-TrkB pathway of the striatum - Xiaotao Liang; Yuewen Ding; Xiaoyu Zhu; Jing Qiu; Xiaoqin Shen; Yifan Xiong; Jieli Zhou; Xiaoshan Liang; Wei Xie (Translational Psychiatry)
Abstract The circadian rhythm system consists of a master clock located in the suprachiasmatic nucleus (SCN) of the hypothalamus and peripheral clocks dispersed throughout other brain areas (including striatum, Str) as well as various tissues and organs. Circadian rhythm disturbance is a major risk factor and common comorbidity for mood disorders, especially anxiety and depression. Bmal1 is one of the fundamental clock protein genes that is required to maintain circadian rhythm. Recent research has revealed a link between suprachiasmatic nucleus dysfunction and anxiety and depression, but the underlying mechanisms remain to be fully elucidated. This study aimed to investigate how circadian rhythm disturbance may lead to anxiety- and depression-like behaviors. Through behavioral tests, virus tracing, molecular biology and other techniques, we found neural connection from the suprachiasmatic nucleus to the striatum. SCN lesions and Bmal1flox/flox + pAAV-hSyn-Cre-GFP (conditional knockout, cKO) mice exhibited disruptions in core body temperature rhythm, as well as anxiety- and depression-like behaviors. Importantly, these mice displayed altered expression patterns of clock protein genes and an upregulation of the Brain-Derived Neurotrophic Factor (BDNF) - Tyrosine Kinase receptor B (TrkB) signaling pathway within the striatum. Microinjection of the TrkB inhibitor ANA-12 can effectively reverse anxiety- and depression-like behaviors. These findings indicate that suprachiasmatic nucleus dysfunction may contribute to the pathogenesis of anxiety and depression through upregulation of the BDNF-TrkB pathway in the striatum, potentially mediated by neural projections from the SCN. Bmal1 gene within SCN may represent a novel therapeutic target for mood disorders.